Profesionalisme Guru di MA Al Ihsan Tanah Grogot: Peran Kepala Madrasah dalam Pembinaan dan Pengembangan - Abdulloh, Mukit; Adiyono, Adiyono (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
The role of the madrasah principal in improving teacher professionalism at MA Al Ihsan Tanah Grogot has been well implemented. This study aims to examine how the madrasah principal carries out and applies strategies to enhance teacher professionalism in the 2023/2024 academic year. This research employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The findings reveal three key aspects: (1) the role of the madrasah principal in improving teacher professionalism, (2) supporting and inhibiting factors affecting the principal’s efforts, and (3) solutions provided by the principal to overcome challenges in professional development. The results indicate that the principal has effectively fulfilled their duties in accordance with operational standards, enabling them to address obstacles and provide appropriate solutions to foster professional teachers. The study suggests strengthening partnerships with educational institutions, optimizing internal resources, and implementing school-based training programs as sustainable efforts to enhance teacher professionalism. Future research is encouraged to explore the long-term impact of these strategies on teaching quality and student learning outcomes.